Effects of capital account openness and trade openness on economic growth - Abdullah, Mohd Faizal (2012)
This study examines the effects of capital account openness and trade openness on economic growth. Consequently, this study investigates the effect of openness on economic growth based on country income level namely, high–income countries, upper–middle income countries, lower–middle income countries and low–income countries. The dataset consist of 52 countries over the period 1990–2007 using a dynamic panel Generalized Method of Moments (GMM) estimation technique. In order to estimate the effect of capital account openness, this study employs three different indicators namely, capital openness (KAOPEN) constructed by Chin and Ito (2009), Quinn index developed by Quinn, (1997) and gross private capital flows. The findings suggest that capital openness (KAOPEN) and Quinn index have positive sign, while gross private capital flows variables has negative sign but these indicators are statistically insignificant. Nevertheless, in terms of sub income country level, capital account openness, through Quinn index has positive effect on economic growth in high–income countries, upper–middle income countries, and lower–middle income countries but has an adverse effect on growth in low–income countries. This study also employs three different indicators of trade openness namely, trade intensity, real trade intensity and new adjusted trade intensity in order to investigate the effect of trade openness on economic growth. Through trade intensity and real trade intensity, trade openness has negative impact on economic growth. However, the new adjusted trade intensity shows the positive effect of trade openness on economic growth. Trade openness has positively effect on economic growth in high–income countries, upper–middle income countries and lower–middle income countries. However, the new adjusted trade intensity demonstrates the adverse effect of trade openness on economic growth. Some contingent variables namely, institutions, financial development and foreign direct investment allegedly would influence the effects of capital account openness and trade openness on economic growth. This study also investigates whether the effect of openness is subject to these three contingent variables by including the interaction term in the model specification. The interaction terms highlight that institutional quality plays a greater role in ensuring the positive effects of capital account openness and trade openness on economic growth. In high–income countries, all these three interaction terms are crucial in influencing the positive effect of capital account openness and trade openness on economic growth. In upper–middle income countries and lower–middle income countries, institutions play a greater role in fostering the positive effect of capital account openness while, institutions and financial development are crucial in influencing the positive impacts of trade openness on economic growth. However, the interaction terms between capital account openness and trade openness with foreign direct investment are insignificant in influencing capital account openness and trade openness in upper–middle income countries and lower–middle income countries. This finding suggests that they should well–managed foreign direct investment before open capital accounts and trade markets, in order to maintaining the greater benefits of capital account openness and trade openness on economic growth.